NILAI PENDIDIKAN TENTANG FENOMENA TOBAT YANG TERULANG: ANALISIS CERAMAH USTADZ ADI HIDAYAT DAN BUYA YAHYA - Salsabilla, Riva Laila; Farzanah, Alifah Putri; Saputra, Wildan; Yunisa, Rahma; Satra, Alihan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
The recurring phenomenon of repentance is a common spiritual dynamic among Muslims, where a person repents but then repeats the same sin. This study aims to analyze the educational values contained in the lectures of Ustadz Adi Hidayat and Buya Yahya regarding this phenomenon. The method used is descriptive qualitative research with a religious discourse analysis approach. Primary data was obtained from videos and transcripts of the sermons of the two figures accessed via YouTube, while secondary data came from Islamic and educational literature. The results of the study indicate that both view repeated repentance not as a spiritual failure, but as an ongoing process of self-education. Ustadz Adi Hidayat emphasizes the importance of knowledge, steadfastness, and self-control in the repentance process, while Buya Yahya highlights the value of divine compassion and sincerity in self-improvement. In conclusion, religious sermons can serve as a reflective educational tool that shapes character through values such as self-reflection, hope, responsibility, and resilience in facing one's weaknesses. These findings contribute to the development of a more humanistic and contextual Islamic education.